Handicapping Males Does Not Affect Their Rate of Parental Provisioning, but Impinges on Their Partners' Turn Taking Behavior - Griffioen, Maaike; Iserbyt, Arne; Müller, Wendt (Frontiers in Ecology and Evolution, 2019)
Parents in biparental bird species have a conflict about how much each of them should invest in the current brood to optimize their reproductive success while not being exploited. Recently, it has been hypothesized that parents might attempt to resolve this conflict via taking turns in their provisioning visits. This implies that an individual will increase its working rate when their partner does, and that they will react with a delay in feeding if the partner starts delaying its visit. Experimental studies testing whether turn taking represents a behavioral strategy are surprisingly scarce and focus on the outcome of turn taking which are alternated visits. However, the adaptive significance of turn taking strongly relies on the response to a partner that increases or reduces care. Therefore, we investigate whether parents use the turn taking rules by performing an experimental manipulation on only one of the parents. To this end, we handicapped male blue tits (Cyanistes caeruleus) by feather clipping and recorded parental feeding behavior. Surprisingly, handicapped males did not have lower visit rates or altered turn taking levels, whilst their female partners had higher visit rates and lower turn taking levels when compared to the control. Females responded to the handicap of their partners, which likely reduced the males’ parental capacity, but the females’ response was independent of the males’ rate of provisioning. Our study highlights that behavioral strategies are flexible within pairs and that these can change at the individual level in response to sudden changes in individual state.